An empirical study to show the relationship between Tech Quotient (TQ) and Academic performance of students - Shaily (International Journal of Advanced Science and Technology, 2020)
Technical/Technology Quotient (TQ) is the ability to incorporate or adapt to changes in technology by creating and implementing methods for effectively integrating technology in day to day functioning. To fully exploit technology, a high TQ requires the right attitude, skills, and decision-making approaches. With rapidly changing technology, it has become important to keep pace with these changes because TQ helps to change the technology mindset as not just being confined to gadgets and apps, but as a way of life. Academic performance of students represents the marks or grades obtained by the students in their college curriculum. It is one of the approaches used by the universities to determine the student’s academic performance in the semester. The main objective of this paper is to investigate the relationship between the Tech Quotient and academic performance of students in B-Schools. A technical quotient assessment test is used as the major instrument to obtain data for this study. A sample size of 104 students has been used from the Pune region for this study. The data has been analysed to compare the technical quotient of the students on the basis of demographics and to determine the relationship between the level of TQ and academic performance of students in B-schools. This study shows a strong positive correlation between the TQ and academic performance for the same. Keywords: Technical Quotient, Academic Performance, Technology